1998
DOI: 10.1148/radiology.209.1.9769842
|View full text |Cite
|
Sign up to set email alerts
|

Human breast lesions: characterization with proton MR spectroscopy.

Abstract: Spatially localized H-1 MR spectroscopy can provide sufficient sensitivity and spectral resolution at 1.5 T to demonstrate Cho in human breast lesions with a spectroscopic protocol that provides up to 1-cm3 resolution. Determining the presence of Cho may provide a useful test for malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
236
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(256 citation statements)
references
References 0 publications
20
236
0
Order By: Relevance
“…The spectra are seen to be different from the normal breast tissue, the water peak dominating with a much lower contribution from lipid protons. This observation is in line with the general hypothesis that tumours have considerably higher water content (Sijens et al, 1988;Gilligam et al, 1997;Jagannathan et al, 1998Jagannathan et al, , 1999Roebuck et al, 1998). Recently, we documented elevated water-to-fat ratios (W/F) in malignant breast tissues compared to normal breast tissues which showed a statistically significant reduction in patients receiving NACT (Jagannathan et al, 1998(Jagannathan et al, , 1999.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The spectra are seen to be different from the normal breast tissue, the water peak dominating with a much lower contribution from lipid protons. This observation is in line with the general hypothesis that tumours have considerably higher water content (Sijens et al, 1988;Gilligam et al, 1997;Jagannathan et al, 1998Jagannathan et al, , 1999Roebuck et al, 1998). Recently, we documented elevated water-to-fat ratios (W/F) in malignant breast tissues compared to normal breast tissues which showed a statistically significant reduction in patients receiving NACT (Jagannathan et al, 1998(Jagannathan et al, , 1999.…”
Section: Resultssupporting
confidence: 84%
“…An increase in phosphomonoester peak in lactating women has also been documented by Twelves et al (1994) through 31 P MRS. Payne et al (1994) have documented that the level of phosphomonoesters changes significantly in normal breast tissues during menstrual cycle. Absolute concentration of choline in breast lesions through in-vivo proton MRS have been determined (Roebuck et al, 1998). Mackinnon et al (1997) reported elevation of choline levels in malignant breast tumours compared to benign cases from in-vivo NMR of FNAB samples and evaluated its sensitivity and specificity in distinguishing benign lesions from invasive cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning MR protocols other than DCE-MRI, diffusion-weighted MR imaging (DWI) and MR spectroscopy (MRS) have recently been reported to demonstrate usefulness in differentiating benign from malignant breast lesions (11)(12)(13)(14)(15)(16)(17)(18). Since the report by Kinoshita et al (11) in 2002, recent studies using DWI have shown that apparent diffusion coefficient (ADC) values can be useful in differentiating between benign and malignant breast lesions (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Breast cancer can be distinguished from benign lesions and from normal breast tissues by a dramatic increase (from undetectable to clearly visible at 1.5 T) of the choline (Cho) signal in 1 H MRS [18][19][20][21][22][23][24][25][26][27][28][29]. Cho, consisting of free, phospho-, glycerophospho-and phospholipidcholine, is a classic in vivo biomarker for cellular proliferation.…”
Section: Introductionmentioning
confidence: 99%